Direct and indirect genetic and fine‐scale location effects on breeding date in song sparrows. (30th August 2016) - Germain, Ryan R.; Wolak, Matthew E.; Arcese, Peter; Losdat, Sylvain; Reid, Jane M.
Summary: Quantifying direct and indirect genetic effects of interacting females and males on variation in jointly expressed life‐history traits is central to predicting microevolutionary dynamics. However, accurately estimating sex‐specific additive genetic variances in such traits remains difficult in wild populations, especially if related individuals inhabit similar fine‐scale environments. Breeding date is a key life‐history trait that responds to environmental phenology and mediates individual and population responses to environmental change. However, no studies have estimated female (direct) and male (indirect) additive genetic and inbreeding effects on breeding date, and estimated the cross‐sex genetic correlation, while simultaneously accounting for fine‐scale environmental effects of breeding locations, impeding prediction of microevolutionary dynamics. We fitted animal models to 38 years of song sparrow ( Melospiza melodia ) phenology and pedigree data to estimate sex‐specific additive genetic variances in breeding date, and the cross‐sex genetic correlation, thereby estimating the total additive genetic variance while simultaneously estimating sex‐specific inbreeding depression. We further fitted three forms of spatial animal model to explicitly estimate variance in breeding date attributable to breeding location, overlap among breeding locations and spatial autocorrelation. We thereby quantified fine‐scale location variances in breeding date and quantified the degree to which estimating such variances affected the estimated additive genetic variances. The non‐spatial animal model estimated nonzero female and male additive genetic variances in breeding date (sex‐specific heritabilities: 0·07 and 0·02, respectively) and a strong, positive cross‐sex genetic correlation (0·99), creating substantial total additive genetic variance (0·18). Breeding date varied with female, but not male inbreeding coefficient, revealing direct, but not indirect, inbreeding depression. All three spatial animal models estimated small location variance in breeding date, but because relatedness and breeding location were virtually uncorrelated, modelling location variance did not alter the estimated additive genetic variances. Our results show that sex‐specific additive genetic effects on breeding date can be strongly positively correlated, which would affect any predicted rates of microevolutionary change in response to sexually antagonistic or congruent selection. Further, we show that inbreeding effects on breeding date can also be sex specific and that genetic effects can exceed phenotypic variation stemming from fine‐scale location‐based variation within a wild population. Abstract : The authors used 38 years of songbird data to estimate sex‐specific additive genetic variances (VA) in breeding date while accounting for fine‐scale location‐based variance (VLoc). They found significant sex‐specific VA, a strongly positive cross‐sex genetic correlation and that modelling VLoc did not alter estimated VA when relatives breed in separate locations.